Enhancing Mathematics Teaching in Open Distance and e-Learning: Effective External Supervision Strategies - Mphahlele, Ramashego Shila; Ngoveni, Mbazima Amos; Mphuthi, Gabriel Tshepo (International Journal of Learning, Teaching and Educational Research, 2024)
This study explores strategies for enhancing mathematics teaching within the context of Open Distance & e-Learning (ODeL) through effective external supervision. The researchers address the critical challenge of ensuring quality teacher preparation in the ODeL context, where student teachers often face unique challenges related to geographical distance, limited resources and minimal direct interaction with external supervisors. Grounded in the principles of experiential learning theory, particularly concrete experience and reflective observation, the study seeks to answer the research question: How can external supervision strategies be effectively designed and implemented to enhance mathematics teaching in open distance and e-learning environments? A qualitative descriptive phenomenology was employed to gain in-depth insights into external supervision. Semi-structured interviews were conducted with a purposive sample of eleven (11) external supervisors, for their extensive experience in supervising student teachers in the ODeL context. Data were analysed thematically, revealing three main categories of challenges: educational, organisational, and interpersonal, encompassing issues such as academic pressure, resource limitations and interpersonal conflicts. The researchers highlight support strategies used by external supervisors, including personalised feedback sessions, mentoring programmes and reflective conferencing. These strategies aim to facilitate the professional development of student-teachers and improve their pedagogical practices in mathematics instruction. The findings underscore the importance of incorporating reflective practices into teacher training programmes, enhancing resources and training, promoting collaboration between educational institutions, and fostering a culture of continuous reflection and growth among student-teachers. This study suggests avenues for effectively enhancing mathematics teaching in ODeL environments through robust external supervision strategies that promote concrete experience and reflective observation. https://doi.org/10.26803/ijlter.23.12.12